DEMERSAL FISH RESOURCES RESULT OF MV. SEAFDEC 2 SURVEY IN THE SOUTH CHINA SEA OF INDONESIA - Wudianto Wudianto; Bambang Sumiono (Indonesian Fisheries Research Journal, 2008)
The South China Sea is belonging to western part of Sunda shelf which consisted of shallow water in the southern part and deep water in the northern part area. The area of Indonesian water in the South China Sea is estimated 595,000 km2 including exclusive economic zone waters.